2019
DOI: 10.1111/omi.12255
|View full text |Cite
|
Sign up to set email alerts
|

Global analysis of lysine succinylome in the periodontal pathogen Porphyromonas gingivalis

Abstract: The gram-negative anaerobe Porphyromonas gingivalis is not only a keystone periodontal pathogen but also an emerging systemic pathogen. Although the newly discovered protein post-translational modification (PTM), lysine succinylation (Ksuc), appears to play an important role in modulating metabolic processes in bacteria, this PTM has not been investigated in P gingivalis. In this study, we used a highly sensitive proteomics approach combining affinity enrichment with high-resolution liquid chromatography coupl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 50 publications
2
20
0
Order By: Relevance
“…Moreover, the GO functional classification and enrichment results for acetylated proteins in the present study were highly similar to that for succinylated proteins (Wu et al., 2019). Notably, enzymes associated with metabolism represented the largest group of both acetylated proteins and succinylated proteins.…”
Section: Resultssupporting
confidence: 86%
See 4 more Smart Citations
“…Moreover, the GO functional classification and enrichment results for acetylated proteins in the present study were highly similar to that for succinylated proteins (Wu et al., 2019). Notably, enzymes associated with metabolism represented the largest group of both acetylated proteins and succinylated proteins.…”
Section: Resultssupporting
confidence: 86%
“…et al have identified 130 Kac sites from 92 proteins in P. gingivalis W50 (Butler et al, 2015). Recently, we have identified 345 Ksuc sites in 233 proteins in P. gingivalis ATCC 33277 (Wu et al, 2019), supporting a possible regulatory role of Kac and Ksuc in P. gingivalis. As previously reported, we further analyzed the overlap between these two PTMs in P. gingivalis (Wu et al, 2019).…”
supporting
confidence: 72%
See 3 more Smart Citations